EFFECT OF AN EDUCATIONAL PROGRAMME ON NURSES’ KNOWLEDGE AND PRACTICE OF PRESSURE ULCER PREVENTION STRATEGIES IN SELECTED TEACHING HOSPITALS IN SOUTH-WESTERN NIGERIA (2014)
Prevention of Pressure Ulcer (PU) is a nursing responsibility and reflects the quality of nursing care. The role of evidence-based Educational Intervention Programme (EIP) among nurses towards its prevention has been differently reported in the literature. However, the possible effects of EIP on PU prevention among nurses in Nigeria have not been adequately explored. This study was aimed at evaluating the effects of an EIP on knowledge and practice of PU prevention among nurses in selected teaching hospitals in Nigeria. A quasi-experimental study was conducted in three of the six teaching hospitals in south-western Nigeria: Lagos State University Teaching Hospital (LASUTH), University College Hospital (UCH) and Obafemi Awolowo Teaching Hospital Complex (OAUTHC). These hospitals were selected through balloting and labeled as Intervention Group (IG)-LASUTH and UCH; and Control (OAUTHC). All 193 nurses (127 in IG and 66 in control group) from the purposively selected wards in neurological, orthopedics and medical units in each hospital were recruited. Participants received a 5-day EIP of five modules focusing on PU risk assessment and preventive interventions with hands-on training. Baseline, immediate post-EIP and 3-month post-EIP knowledge of PU prevention strategies were evaluated using a standardised Pressure Ulcer Knowledge Test (PUKT). Practice was assessed using a validated observational checklist (Risk-based Prevention Intervention Checklist) at baseline and 3-month post-EIP. During the 3-month period, consumables for skin care and prevention of friction were also provided for use on the skin of patients at risk for PU in the IG and control group. Paired t, Mann-Whitney U and Wilcoxon Sign tests were used for data analyses. There were no significant differences in the mean ages of participants [IG: 36.3±10.4 years; control: 35.2±11.9 years] p<0.05, and mean years of experience [IG: 14.5 ±13.7 years; control: 12.6 ±12.0 years] p<0.05. The mean knowledge scores increased significantly among IG from 32.5 ±4.2 at baseline to 40.7 ±3.4 (p<0.05) at immediate post- EIP while in the control group it increased from 30.8± 5.0 to 31.2 ±5.2. At 3-month post-EIP, the mean score increased significantly in both groups; from 40.7±3.4 to 42.0 ± 4.0 in the IG and 31.2±5.2 to 37.8 ± 5.6 in the control group. The increased mean knowledge scores from baseline to immediate post-EIP among IG (8.2 ±5.4) was significantly higher than that of the control group (0.4 ±2.2); (p < 0.05). The increased mean knowledge scores from immediate post-EIP to 3-month post-EIP among IG (2.0 ±5.5) was not significantly different from the control (6.2 ±7.2). The median rank for practice in both IG and control groups were equal (97.0) at baseline and it increased to 105.0 only in the IG at 3months (p<0.05). However, in the control group the median rank decreased to 87.5 at 3-month post-EIP (p<0.05). Educational Intervention Programme improved nurses’ knowledge of pressure ulcer prevention and practice. There is the need to improve on existing nursing continuing education programmes on evidence-based educational intervention for pressure ulcer prevention.